2020
DOI: 10.1017/s0959269520000010
|View full text |Cite
|
Sign up to set email alerts
|

What vocabulary size tells us about pronunciation skills: Issues in assessing L2 learners

Abstract: Measures of second language (L2) learners’ vocabulary size have been shown to correlate with language proficiency in reading, writing and listening skills, and vocabulary tests are sometimes used for placement purposes. However, the relation between learners’ vocabulary knowledge and their speaking skills has been less thoroughly investigated, and even less so in terms of pronunciation. In this article, we compare vocabulary and pronunciation measures for 25 Italian instructed learners of L2 French. We measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…The vowels produced by the learners in the high vocabulary group as compared to the low vocabulary group were more accurately identified as the intended target by listeners, and vocabulary size as a continuous measure was a significant predictor of average intelligibility, unlike years of English study or length of stay in Australia. Similarly, Mairano and Santiago (2020) reported that vocabulary size correlated moderately with fluency measures and ratings of accentedness. In addition, one study has examined the relationship between L2 vocabulary size and lexical encoding.…”
Section: Second Language Vocabulary Sizementioning
confidence: 88%
“…The vowels produced by the learners in the high vocabulary group as compared to the low vocabulary group were more accurately identified as the intended target by listeners, and vocabulary size as a continuous measure was a significant predictor of average intelligibility, unlike years of English study or length of stay in Australia. Similarly, Mairano and Santiago (2020) reported that vocabulary size correlated moderately with fluency measures and ratings of accentedness. In addition, one study has examined the relationship between L2 vocabulary size and lexical encoding.…”
Section: Second Language Vocabulary Sizementioning
confidence: 88%
“…It seems reasonable to assume that front rounded vowels can be assimilated to the corresponding primary cardinal vowels, i.e., either unrounded front vowels /i/, /e/, /E/, or rounded back vowels /u/, /o/, /O/. There is evidence in the literature that /y/ tends to be assimilated to /u/ by English L1 (Ruellot 2011;Darcy et al 2012;Liakin et al 2015;Melnik-Leroy et al 2022), Spanish L1 (Racine and Detey 2018), and Italian L1 learners (Pillot-Loiseau and Grando 2020); however, it seems that English L1 learners tend to assimilate /ø/ -/o/ (Darcy et al 2012), while Spanish L1 and Italian L1 learners tend to assimilate /ø/ -/e/ (Kartushina and Frauenfelder 2014;Mairano and Santiago 2020). Therefore, we tested mid front rounded vowels against the corresponding back rounded vowels for English L1 learners, and against front unrounded vowels for Spanish L1 and Italian L1 learners.…”
Section: Selection Of Vowel Contrastsmentioning
confidence: 99%
“…In order to quantify the overlap of realizations for target vowel pairs, we computed Pillai scores. This score has been used in the literature to evaluate the degree of vowel mergers and splits [22] and to assess L2 pronunciation [23,24]. Pillai scores range from 0 (complete overlap of categories) to 1 (complete separation of categories).…”
Section: Acoustic Metrics For Assessing L2 Vowel Accuracymentioning
confidence: 99%